Weed survey of spring cereals in New Brunswick - Thomas, A.G.; Doohan, D.J.; McCully, K.V. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1994)
During 1986 and 1987, a weed survey of 187 New Brunswick cereal fields was conducted. A total of 76 species were identified of which 40 were considered agronomically important. About 50% of the species were perennial. Hemp-nettle (Galeopsis tetrahit), quack grass (Agropyron repens), sheep sorrel (Rumex acetosella), ox-eye daisy (Chrysanthemum leucanthemum), corn spurry (Spergula arvensis), and chickweed (Stellaria média) had the highest relative abundance values. Quack grass and hemp-nettle had the highest densities at 8.0 and 7.1 plants m-2, respectively. The highest weed density (103 plants m-2) was found in oats (Avena sativa) grown after a forage crop. The lowest density (24 plants m-2) was found in wheat (Triticum aestivum) grown after potatoes (Solarium tuberosum). Most of the abundant species were tolerant to MCPA, the most commonly used herbicide. Farmers could make major improvements in cereal weed control by choosing a herbicide that would control species tolerant to MCPA or 2,4-D, and using preplant or postharvest weed control to minimize the impact of perennial weeds.